Molecular phylogeny of trematodes in Family Heterophyidae based on mitochondrial cytochrome c oxidase subunit I (mCOI) - Thapana Chontananarth (2018)
Objective: To analyze a phylogenetic tree for understanding the molecular systematic of trematode in Family Heterophyidae, which are highly distributed in Thailand. Methods: Based on thirteen sequences of mitochondrial cytochrome c oxidase subunit I (mCOI) gene from six genera of heterophyid trematodes, viz. Haplorchis, Stellantchasmus, Centrocestus, Metagonimus, Pygidopsis, and Haplorchoides were aligned automatically using the Clustal × 2.0 program. A phylogenetic tree was constructed by maximum likeinghood (ML) and neighbor-joining (NJ) methods, with 1 000 bootstrap using the 5.0 program. Results: The phylogenetic relationship from both methods was similar and separated into three groups consisting of Haplorchoides pumilio group, Haplorchoides taichui group and another heterophyid genera. Conclusions: The sequence data of mtCOI can be used to investigate the phylogenetic relationships of trematodes at the genus level. Each clade of different genera of heterophyid trematodes can be separated into sister groups that correlated with the morphological characteristic, kind of secondary intermediate host and geographic distribution. © 2014 Hainan Medical College.